Body condition score, body measurement and carcass characteristeics of beef cattle in Felda - Ahmat Sharezza Ahmat Ja'affar (2016)
A study was conducted to evaluate body condition acore (BSC) of beef cattle under cattle-oil palm integrated production system. This study focused on Kedah-Kelantan crosses and Brahman crosses cattle reared by the farmer at FELDA Papan Timur, Kota Tinggi, Johor. The general objective of the study is to evaluate the management of integrated cattle farming in the study area. Other than that, the study is focusing more on examining the relationship between BCS, body measurements and carcass characteristics of beef cattle in FELDA integrated production system. Besides that, by determining the factors that can improve the carcass quality of cattle and developing suggestions that can improve the quality of cattle, focuses of the study can be achieved. A total of 100 beef cattle were evaluated under the integration system with oil palm plantation. Body weight (BW), body condition score (BSC), digital photograph, body measurements (BMs), carcass weight (CW) and dressing percentage (DP) were collected in total of 35 slaughtered animals during the study. Four parameters of BMs collected during the study were width of hindquarters (WO), lengtj oh body (LB), tail head to the hock (TH) and heart girth (HG). The sample size of 35 encompassed of BCS range from 3 to 7. The result in percentages according to the BCS are at 6 (57.1%), 5 (31.4%), 7 (5.7%), 3 and 4 (2.9%). The highest BW of beef cattle among 100 samples and 35 samples was 435 kg, whereas the lowest BW of beef cattle were 151 kg out of 100 samples and 200 kg out of 35 samples. The BW of 35 slaughtered beef cattle was highly correlated with the BCS (R²= 0.84). Regression analysis between BMs and BCS of 35 animals showed that LB, HG and WQ were highly correlated indicated by the R² values of 0.82, 0.84 and 0.82 respectively. The CW and DP of 35 slaughtered beef cattle were also highly correlated with BCS indicated by the R² values of 0.88 and 0.82 respectively. The VW of 35 slaughtered beef cattle was highly correlated with its BW (R²= 0.985). For the marbling score of Longissimus Dorsi muscle of 35 slaughtered beef cattle, the average score was 1 out of 11 which was low. For the average fat colour score of carcass among the 35 animals, the result was pale yellow colour. The average fat thickness of the Longissimus Dorsi muscle among the 35 slaughtered beef cattle was 0.3 cm. The result of rib eye muscle area among the 35 samples was 85 cm² in average. For the meat colour score among the 35 slaughtered beef cattle, the result was red colour. The result of dry matter content of Longissimus Dorsi muscle among the 35 slaughtered beef cattle was 26.12%. The average dry matter (DM) of forages under oil palm plantation in FELDA Papan Timur, Kota Tinggi was 16.65%. The dry matter content of Axonopus compressus, Paspalum conjugatum, Ottocholoa nodosa, Eleuisine indica and Chrysopogen aciculatus were 17.34%, 15.44%, 16.5%, 17.54% and 16.44%, respectively. Farmers used free grazing system for rearing beef cattle under oil palm plantation. BCS of beef cattle were moderate which was BCS 5 (61 observation=61%). There were no BCS 1 and 2 observed in this study area which was indicating poor BCS. From the findings, it can be suggested that beef cattle can be reared under oil palm plantation as long as they are provided with sufficient feeds and proper management.